"Qi Nan" agarwood restores podocyte autophagy in diabetic kidney disease by targeting EGFR signaling pathway - Ning Li; Xuenan Liu; Hao Wang; Yingling Duan; Yu Zhang; Ping Zhou; Haofu Dai; Tian Lan (BMC, 2024)
Abstract Background Diabetic kidney disease (DKD) is a microvascular complication of diabetes mellitus, contributing to end-stage renal disease with limited treatment options. The development of DKD is attributed to podocyte injury resulting from abnormal podocyte autophagy. Consequently, the restoration of podocyte autophagy is deemed a practicable approach in the treatment of DKD. Methods Diabetic mice were induced by streptozotocin and high-fat diet feeding. Following 8 weeks of "QN" agarwood treatment, metrics such as albuminuria, serum creatinine (Scr), and blood urea nitrogen (BUN) were evaluated. Renal histological lesions were evaluated by H&E, PAS, Masson, and Sirius red staining. Evaluation of the effects of "QN" agarwood on renal inflammation and fibrosis in DKD mice through WB, q-PCR, and IHC staining analysis. Cytoscape 3.7.1 was used to construct a PPI network. With the DAVID server, the gene ontology (GO) functional annotation and the Kyoto encyclopedia of genes and genomes (KEGG) signaling pathways of the target enrichment were performed. Molecular docking and binding affinity calculations were conducted using AutoDock, while PyMOL software was employed for visualizing the docking results of active compounds and protein targets. Results The results of this study show that "QN" agarwood reduced albuminuria, Scr, and BUN in DKD mice, and improved the renal pathological process. Additionally, "QN" agarwood was observed to downregulate the mRNA and protein expression levels of pro-inflammatory and pro-fibrotic factors in the kidneys of DKD mice. Network pharmacology predicts that "QN" agarwood modulates the epidermal growth factor receptor (EGFR) signaling pathway. "QN" agarwood can increase the expression of LC3B and Nphs1 in DKD mice while reducing the expression of EGFR. Conclusion The present study demonstrated that "QN" agarwood ameliorated renal injury in DKD by targeting EGFR and restoring podocyte autophagy. Graphical Abstract